Literacy Study of the Influence of Immoral Actions in Educational Institutions on the Formation of Students' Character - Qomarrullah, Rifiy; Mujadi, Mujadi; Tammubua, Milcha H.; Suratni, Suratni; Muhammad, Rivaldhy N.; Widyanto, Zainal; Nia Betaubun, Restu Monika (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to examine the influence of amoral actions in educational institutions on the character formation of students. In the context of education, amoral actions are often overlooked, yet they can significantly impact the moral and ethical development of students. The research employs a qualitative approach, utilizing data collection techniques such as interviews, observations, and document studies in several schools. The findings reveal that amoral actions, such as bribery, intimidation, and discrimination, have a significant negative impact on the character of students. Students exposed to amoral behavior tend to show a decline in moral and ethical values and experience difficulties in building healthy social relationships. This research also finds that a supportive educational environment that promotes positive values plays a crucial role in fostering good character. These findings are expected to serve as a consideration for schools and policymakers in creating a more ethical and moral educational environment for the better character formation of students.